A Proteomics‐Driven Assay Defines Specific Plasma Protein Signatures in Different Stages of Ménière's Disease. Issue 6 (June 2014) - Chiarella, G.; Di Domenico, M.; Petrolo, C.; Saccomanno, M.; Rothenberger, R.; Giordano, A.; Costanzo, F.; Cassandro, E.; Cuda, G.
ABSTRACT Ménière's disease (MD) is a common disorder of the inner ear whose hallmarks are vertigo, tinnitus, aural fullness, and progressive hearing loss. The degree of severity of the disease is quite heterogeneous, and so is its pathogenesis. A multifactorial inheritance of intrinsic and extrinsic factors has been described, but there is not a common agreement on the molecular basis of MD. In a recent article, we have demonstrated that patients suffering from MD share a common plasma proteomic signature, characterized by the presence of several up‐ and down‐regulated proteins. In this study, we have further extended our analysis and show that the differential expression of plasma proteins can identify specific subsets of MD‐affected individuals, depending on their stage. Our findings confirm our plasma proteomics‐driven approach as a powerful tool for early diagnosis of MD and uncover a potentially starring role for some proteins in the development and fate of this frustrating disease, whose pathogenesis still remains unclear. J. Cell. Biochem. 115: 1097–1100, 2014. © 2013 Wiley Periodicals, Inc.